Análisis del proceso de atención a los usuarios del Servicio de Rentas Internas, Agencia Babahoyo, periodo 2020 - Mora Arregui, Miriam Adela (2020)
This study deals with the analysis of user care in the Internal Revenue Service, Agencia Babahoyo, it is necessary to consider that this entity has improved the quality of the service in recent years, however, it still faces certain challenges that need be approached with a social commitment to achieve results that benefit the entity, but also the taxpayers. The objective of the research is to analyze in detail the process of customer service to detect the weaknesses that arise, in such a way that this study contributes to the generation of strategies for the improvement of the service. This is a quantitative approach research by virtue of the analyzed variable, the type of research is descriptive, the methods used are: inductive and deductive, the techniques used: observation and survey, while the instrument through which the Information from the primary sources are the observation card and the survey questionnaire. The results obtained during the investigative process show that the main weakness that influences the attention to users is the lack of personnel in the Taxpayer Assistance Area. The conclusions reached in the case study is that citizens need to obtain empowerment regarding the procedures that can be carried out on the virtual platform to avoid agglomeration of taxpayers in the entity's facilities.